The Impact of US Trade Sanctions on the Global Trade of Target Countries: Do the Political Institutions of the Targets Matter? - Sajjad Faraji Dizaji; Mohammad Reza Farzanegan (Center for Economic Studies and ifo Institute (CESifo), 2024)
We investigate the effects of US-imposed trade sanctions on the global trade patterns of sanctioned countries by employing a gravity model that incorporates data spanning from 1980 to 2020 across 79 nations. The results reveal that both partial and complete US sanctions lead to significant reductions in bilateral trade between the US and target countries as well as between target and third countries. A unit increase in the intensity of complete trade sanctions in place reduces US bilateral trade flows with its sanctioned trading partners by about 76 percent while a unit increase in the intensity of partial US sanctions decreases trade by 16 percent. When complete export and import sanctions are implemented, US bilateral trade flows with its sanctioned trading partners witness a staggering decline of about 90 percent and 39 percent, respectively. In contrast, the application of partial export and import sanctions leads to a decrease in trade by 13 percent and 17 percent, respectively, all other factors remaining constant (ceteris paribus). Moreover, we show that target countries with stronger political institutions, as measured by democracy indicators, manage to alleviate some of the adverse effects of US sanctions on bilateral trade with both the US and third countries.
Keywords: D74; F14; F51; O24; O43; 330; sanctions; trade; import; export; democracy; political institutions; gravity model